La electricidad en las relaciones España-Portugal - Marín, Cayetano Espejo (Finisterra, 2004)
From the early 1960s onwards, Spain and Portugal have maintained far-reaching programs for the exchange of electric power. These contacts have afforded, on the one hand, an increase in the security of electricity supply for both countries and, on the other, a better exploitation of their particular energy resources. The likely launching of the Iberian Electricity Market in April 2004 will lead to a new phase in the relations between Portugal and Spain. The new Market is based on three essential elements: i) the expansion of electric links along their shared national borders, ii) the setting up of a lone Operator for the single Iberian Market and iii) the coordination of the two Operators that exist nowadays, RED ELÉCTRICA DE ESPAÑA and REDE ELÉCTRICA NACIONAL. The Iberian Electricity Market will be the first to comprise countries of the European Community only and it will generate one-tenth of the electric power consumed in Europe, being the fourth largest producer.